The increasing need for Geographical Information Technology (GIT) tools in Geoconservation and Geotourism - Mark Williams; Melinda McHenry (Geoconservation Research)
The use of GIS, remote sensing, and other geographic tools in geoconservation and geotourism is increasing. These tools – hereafter referred to as ‘Geographic Information Technology’ (GIT) tools – have the potential to simplify workflow in geoconservation assessment and inventory, be employed as decision support and decision making tools for complex decisions, or be used to enhance communication and user experience in geotourism. In this paper, we review the progress on the use of GIT tools in geoheritage and geotourism to date, highlighting current gaps in practice. By way of an interview of prominent global geoconservation and geotourism professionals conducted in 2018, we show that approximately 25% of the surveyed workforce use some type of GIT tool to aid in decision support, decision making, or for communication(s) of inventory elements and features of interest. Upon review of the literature, it appears that the vast majority of tools are used for communications of inventory, features and site maps. Opportunities for further improvement in the field will most likely be realised when more sophisticated decision-making tools become available for geoconservationists and geotourism professionals, especially in the use of GIS Multi-Criteria Decision Analysis (GIS-MCDA) to rank and curate inventory, geosites or geotouristic experiences. We conclude our discussion with a case study demonstrating the use of selected GIT tools in the process of decision support, decision-making, and communications. We show that at each step in the process of geoconservation, there is a GIT tool that can simplify workflow, and be used to cross-collaborate with other users or platforms. With further refinement, GIT tools should be able to support geoconservationists and geotouristic professionals in global decision making – for assessment, inventory, and standardisation of interpretations of landscape values and potential use.